Smart Smoke and Air Quality Detection System - Rosli Bin Yusop, Caleb Tochukwu Raluchukwu Ozoh, R.Dhakshyani (International Journal of Advanced Science and Technology, 2020)
The gradual increase in fire disasters is alarming which calls for concerns, and it creates tension among the public due to the uncertainty of the safety of people’s lives and properties in an event of fire outbreak. These accidents are caused mainly due to the slow detection of fire by the existing smoke detectors, the uni-functionality of the existing smoke sensor (ability to detect only a single gas) and lack of proper forewarning to contain the fire before it becomes a mass fire. A smart smoke and air quality detection system is required which has a significant surveillance system to detect and control the fire and fire causing agents automatically using cloud-based Internet of Things (IOT) and data analysis. This requirement has been accomplished in this proposed system by employing smoke detection system, fire controlling system and an air quality management system using Arduino ESP8266 NodeMCU. The system enables real-time monitoring of the fire, smoke level, temperature and air quality by and IOT GUI and notifies the user and relevant authorities by SMS and email of fire affected area with GPS coordinates and gives the real-time updates of room temperature from time to time. The sensor data sent to the cloud is stored and exported to a MySQL database for further data analysis. The proposed system has been tested to have an average detection time from 33 samples of 10.32seconds for 33.51ppm of smoke. As future enhancement, a Machine Learning (ML) technique can be used to develop a forecasting model for early fire prediction based on real-time and historical sensor data.